Photo‐switchable Fluorescence in Hydrogen‐Bonded Liquid Crystals - Kappelt, Alexander (Chemistry, 2020)
A series of hydrogen‐bonded liquid crystals showing switchable fluorescence is reported. The fluorescence behavior results from the unique combination of hydrogen bonding, liquid crystallinity, and photobasicity. Thus, the molecular mobility in the mesophase is essential for the reversible photo‐initiated proton transfer switching on the fluorescence of the assemblies. The application potential of the materials for photo‐patterning was demonstrated.